Apoptosis deregulation expression in Philadelphia-negative Myeloproliferative Neoplasms in a Portuguese population - Azevedo, Ana Paula (2017)
Poster presented at the 7th International Conference on Myeloproliferative Neoplasms / European School of Haematology. 27-29 October 2016. Estoril, Portugal